2016
DOI: 10.1371/journal.pone.0167012
|View full text |Cite
|
Sign up to set email alerts
|

Are Older Adults Physically Active Enough – A Matter of Assessment Method? The Generation 100 Study

Abstract: IntroductionPhysical activity (PA) is beneficial for general health. As a result, adults around the world are recommended to undertake regular PA of either absolute or relative intensity. Traditionally, adherence to PA recommendation is assessed by accelerometers that record absolute intensity thresholds. Since ageing often results in a decrease in cardiorespiratory fitness (CRF), older adults (aged > 65 years) might be more susceptible to not meeting the PA recommendation when measured in absolute terms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Poor weather conditions might augment these concerns and thereby reduce outdoor PA among this age group. Notably, outdoor recreational walking is the most common PA type among older adults in Norway [ 13 ]. This might be a reasonable explanation as to why the weather, in the current study, explained more of the variance in PA in warmer versus the colder months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor weather conditions might augment these concerns and thereby reduce outdoor PA among this age group. Notably, outdoor recreational walking is the most common PA type among older adults in Norway [ 13 ]. This might be a reasonable explanation as to why the weather, in the current study, explained more of the variance in PA in warmer versus the colder months.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon a previous study in this population [ 13 ], the participants in the current study was categorized into unfit (25% lowest; Males <27.0 mL·kg -1 ·min -1 , females <23.6 mL·kg -1 ·min -1 ), moderately fit (50% medium; males 27.0–35.6 mL·kg -1 ·min -1 , females 23.6–29.8 mL·kg -1 ·min -1 ), and highly fit (25% highest; males high >35.6 mL·kg -1 ·min -1 , females high >29.8 mL·kg -1 ·min -1 ) individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that aimed to improve the insight into the preventive role of objectively measured PA and health‐related conditions at older ages have applied thresholds validated in healthy young adults for PA intensity categorization . This could have led to inaccuracy and misclassification of actual PA behaviours, generating an overestimation of SB and underestimation of actual PA, due to differences in energy cost of a given activity in older adults, when compared with younger cohorts . It has already been demonstrated that using classical younger adults' cut‐points when exploring older adults' PA patterns can artificially decrease PA adherence rates among older adults and that PA estimates vary notably depending upon the cut‐points used …”
Section: Introductionmentioning
confidence: 99%
“…8,9 This could have led to inaccuracy and misclassification of actual PA behaviours, generating an overestimation of SB 10 and underestimation of actual PA, 11 due to differences in energy cost of a given activity in older adults, when compared with younger cohorts. 12 It has already been demonstrated that using classical younger adults' cut-points when exploring older adults' PA patterns can artificially decrease PA adherence rates among older adults 12,13 and that PA estimates vary notably depending upon the cut-points used. 14 Recently, isotemporal substitution models were introduced to the analysis of PA data.…”
Section: Introductionmentioning
confidence: 99%
“…The confirmation of being notified of acceptance for the wait‐list might create a period of optimism and life satisfaction (ceiling effect), but this should have been similar for both genders. It is possible that the reduction in physical function and the loss of freedom is experienced differently for men than women in this elderly population . Both genders experience a worsened HRQoL during the first year on the waiting list suggesting that the waiting time and the reduced kidney function may itself be a burden …”
Section: Discussionmentioning
confidence: 99%